Evolution of Ayushman Bharat Scheme: A Case Study of Chhattisgarh State - Dr. Falendra Kumar; Prof. L. S. Gajpal (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The Pradhan Mantri Jan Arogya Yojana (PMJAY), popularly known as the Ayushman Bharat Scheme, is one of India’s largest public health insurance initiatives aimed at providing financial protection to economically weaker sections. Despite wide coverage, regional disparities exist in terms of availability and utilisation of Ayushman Cards. The present study examines the availability, usage pattern, and hospital-wise utilisation of Ayushman Cards in selected rural areas of Chhattisgarh. Primary data were collected from 317 respondents across four districts—Raipur, Rajnandgaon, Janjgir-Champa, and Dantewada. The findings reveal that although a majority of respondents possess Ayushman Cards, actual utilisation remains low, with government hospitals being the preferred choice. The study highlights the need for increased awareness and improved healthcare infrastructure, especially in tribal and backward regions.